Hive o esquadrão químico: uma proposta de jogo didático para o ensino de química orgânica - Dias, Raquel Rodrigues (2021)
This study focused on the construction of a didactic game, based on the principles of the STEAM methodology (Science, Technology, Engineering, Arts and Mathematics), aimed at teaching organic chemistry. For that, a board game was created, in two modes, the normal game mode, very similar to board games found in literature, and the STEAM game mode, this one improved and within the STEAM proposal, which aims to stimulate learning in various simultaneous fronts, more comprehensively and without the segmentation commonly observed in the classroom context. The “HIVE game: The Chemical Squad”, was tested and evaluated by experts in the field of chemistry, including undergraduate students, teachers of basic and higher education. The guests were able to play and evaluate by answering a questionnaire, which had validation criteria based on the subjects' reaction to the educational game, adapted from Kirkpatrick, to support the measurement of the reaction, were included in this structure, the ARCS model for evaluating the level of motivation and user experience components in games (UX), for evaluating the experience of using the game. After its evaluation, it was possible to verify that the game presents itself as a potential tool to assist in teaching organic chemistry, since the level of engagement of players surpassed 90%. In addition, the immersion capacity and the variety of mechanics left the most dynamic and interesting game. The use of the STEAM methodology was a positive point, as the synergy with other areas of knowledge created an immersive, cooperative and conducive environment to develop players' skills and competences. It is hoped, therefore, that this educational resource favors and enhances the teaching of organic chemistry, inspiring the dissemination and creation of new playful teaching materials along the same lines.